Écouter et voir dans un monde technique : Effets de la discontinuité des horaires sur l’activité de travail des infirmières - Ana-Maria Seifert; Karen Messing (Perspectives Interdisciplinaires sur le Travail et la Santé)
The structure of work schedules and its effects on the work activity of health care workers in a short-term care facility were analyzed in a context of changes to the Québec health care system. The analysis revealed short patient stays and a great discontinuity in work periods for nursing personnel : 60 % of health care workers in one department worked for fewer than five shifts per month in this department. Thus, the workers often have little information on patients, and the constant changes in the work teams can affect the strategies that they use to remedy the situation. Since the “technical” aspects of the work cannot be reduced, the more “human” aspects can be compressed. Could this type of work organization diminish caring, thus depriving patients of important human contact and health care workers of their sense of the meaning of their work. Could this loss of meaning affect the absenteeism rate, which is known to be high among nurses ?